A new multilevel buck-boost inverter structure using six active switches - Leonardus Heru Pratomo; Florentinus Budi Setiawan; Sushil Paudel (National Research and Innovation Agency, 2026)
Generally, multilevel inverters function as voltage step-down or step-up converters. This paper discussed a new type of multilevel inverter, specifically five-level and seven-level designs that use six active switches, which can increase or decrease the output voltage. The first study on using equal DC sources (E + E), known as symmetric, in the five-level setup for adjusting voltage was conducted, and then it was expanded to seven levels using an uneven DC source (2E + E), called asymmetric, with a new control method that works differently for each function. This multilevel voltage step-up (boost) and step-down (buck) inverter fundamentally has two components: a DC voltage level generator and a voltage step-up and polarity generator. This work provides a detailed look at how the multilevel voltage boost and buck inverter is built to show the features of the suggested design. Simulation data is provided to confirm how well each proposed design works with five-level and seven-level voltage increases and decreases in an inverter, using the sinusoidal pulse-width modulation (PWM) index and PWM duty cycle for better understanding. By the simulation, the total harmonic distortion (THD) value of the inverter when it operates as a buck is 1.26-1.32 %, and when it operates as a boost, it is 1.32-1.36 %. These values are still below 5 % in accordance with IEEE 519 standards and demonstrate a unity power factor.